2020
DOI: 10.5751/ace-01692-150219
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation patterns shape population structure of the Magellanic Woodpecker (Campephilus magellanicus) in southern Chile

Abstract: One important landscape-scale consequence of deforestation is reduced connectivity, which has the potential to isolate populations in ways that affect genetic diversity and population structure. Among the many regions of the world where this scenario has played out is the South American temperate forest (SATF) in southern Chile, and there is now strong concern about the population viability of forest taxa. We studied one such species, the Magellanic Woodpecker (Campephilus magellanicus), a forest specialist th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies have shown that woodpecker species can have similar or different drumming types [24][25][26][27] . Furthermore, many researches have reported that species richness and behaviour of woodpecker are strongly in uenced by tree availability and landscape 19,20,21 . Therefore, more variations of drumming types may be discovered, even within species, using observational studies.…”
mentioning
confidence: 99%
“…Studies have shown that woodpecker species can have similar or different drumming types [24][25][26][27] . Furthermore, many researches have reported that species richness and behaviour of woodpecker are strongly in uenced by tree availability and landscape 19,20,21 . Therefore, more variations of drumming types may be discovered, even within species, using observational studies.…”
mentioning
confidence: 99%